Factors influencing headway selection while negotiating secondary tasks in real-traffic - Li, Xi (My University, 2010)
Recently, naturalistic studies have been able to relate a large amount of rear-end crashes to driver‟s inattention while following another vehicle. Several simulator-based researches have claimed that drivers get a longer mean-reaction-time while doing a secondary task. However, very few studies on drivers‟ headway selection while performing a secondary task during car-following in real-traffic have been done. Therefore, this study aims to discover whether drivers increase time headway to a forward vehicle while negotiating a secondary task by using a naturalistic and field operational test database. This study was conducted using the Volvo Car data from SeMiFOT database. SeMiFOT is a Naturalistic and Field Operational Test study which was carried out by 12 different partners in Sweden from January 2008 to December 2009[1]. The methodology followed in this investigation comprised of four steps. In the first step, all the known secondary tasks from the literature were classified into nine categories based on their different characteristics. Then the nine secondary tasks were assigned to three different levels: complex task, moderate task, and simple task; according to the number of required button-press and/or eye-glance; in the second step, videos were manually reviewed to mark all the following action periods containing secondary task events; in the third step, data incorporating vehicle following and secondary tasks was imported into Matlab for further analyses, more specifically, four variables were selected from the VCC database: time index, headway distance, vehicle speed, and adapted cruise control lamp status, moreover, time headway was selected as the standard measure in this study; finally, in the fourth step, mean values of time headway for all selected events were compared in order to derive different headway selection for different secondary task related periods. The results concluded in this study can be used as an indicator which points out which factors may have influence on drivers‟ headway selection while negotiating secondary tasks during car-following in real-traffic.
Keywords: Farkostteknik; Kognitionsforskning; Vehicle Engineering; Cognitive science